PERENCANAAN PENGEMBANGAN E-GOVERNMENT DALAM PENYELENGGARAAN PEMERINTAHAN DAN LAYANAN PUBLIK DI KOTA SOLOK - Mardahayati, Mrs. (FIA UB, 2012)
This study aims to describe and analyze (1) Development planning of Solok cityâs e-government, (2) Implementation of e-government development plan in governance and public services in the City of Solok 2010, (3) Enabling and inhibiting factors in implementing e-government development plans in the City of Solok. This study used a qualitative descriptive method where source of the data came from informants and documents. Result of the research indicates that Development planning of Solok cityâs e-Government is a top-down planning. The ideas came from the Secretariat of Public Relations Solok which has resulted a Masterplan of e-Government development on Solok city Local Government 2010-2014. Implementation of e-government development plan in 2010 has been largely referring to the masterplan, but not completely in accordance with the map stages that have been made since the implementation is adjusted by some factors such as needs and opportunities. Supporting factors in the implementation of e-government development plans not only have already had a masterplan as a reference, but also the good commitments that the leaders have. Besides, motivations of the e-government application users take important roles in improving the performance of each work unit. While the constraining factors are the competence of human resources, inadequate infrastructure, limited budgets, lack of coordination, and the role of ICT management units in implementing e-government plan on Solok city is not optimal yet.